2019
DOI: 10.1371/journal.pone.0218206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebrovascular reactivity in chronic hepatitis C patients using transcranial color Doppler

Abstract: Hepatitis C viral (HCV) infection is associated with systemic inflammation and metabolic complications that might predispose patients to atherosclerosis, including cerebrovascular atherosclerosis. The aim of this study was to assess cerebrovascular reactivity in patients with chronic hepatitis C. Seventeen patients with chronic hepatitis C infection, as well as 11 healthy blood donors in the control group, were assessed for cerebrovascular reactivity according to the well-established breath-holding test that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our study showed that cerebrovascular reactivity values, calculated as the BHI, were significantly lower in the HCV group than in the healthy control group. Similar results were obtained in our previous study which consisted only of ultrasound parameters, emphasising reduction of vasodilatatory capacity of the cerebral arteries in patients with chronic hepatitis C ( Pavicic Ivelja et al, 2019 ). The above mentioned findings suggest an unfavorable effect of chronic HCV infection on cerebrovascular hemodynamics and might lead to an increased risk of CVD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed that cerebrovascular reactivity values, calculated as the BHI, were significantly lower in the HCV group than in the healthy control group. Similar results were obtained in our previous study which consisted only of ultrasound parameters, emphasising reduction of vasodilatatory capacity of the cerebral arteries in patients with chronic hepatitis C ( Pavicic Ivelja et al, 2019 ). The above mentioned findings suggest an unfavorable effect of chronic HCV infection on cerebrovascular hemodynamics and might lead to an increased risk of CVD.…”
Section: Discussionsupporting
confidence: 90%
“…Ultrasound data were collected as previously described in Pavicic Ivelja et al (2019) using transcranial color Doppler sonography (TCCD) which allows a rapid and non-invasive investigation of cerebral blood flow (CBF) velocities in the large cerebral arteries and velocity changes after a vasodilatory stimulus such as apnea. These changes, known as cerebrovascular reactivity, are considered an indicator of the capability of adaptive changes in CBF and can be reduced in patients under risk of CVD ( Markus & Harrison, 1992 ; Silvestrini et al, 1996 ; Apruzzese et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like other virus infections, the SARS-CoV-2 virus can cause severe endothelial dysfunction. Pavicic Ivelja et al found that chronic hepatitis C patients have altered cerebrovascular reactivity and these negative effects on cerebrovascular hemodynamics could contribute to the increased risk of cerebrovascular disease [ 30 ]. Chow et al found similar changes in patients with HIV infection and their cerebrovascular endothelial dysfunction may independently contribute to cognitive impairment [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also considered the potential association between HCV infection and cerebrovascular events, finding contradictory results, ranging from HCV infection as a risk factor to HCV infection as a protective factor [142][143][144]. Despite the heterogeneity found among the studies included in a meta-analysis (made up of six studies, five retrospective and one prospective) published in 2013, results suggested that HCV infection increases the risk of stroke; with a random-effects model, the outcome was 1.58 (0.86, 2.30), which was improved after excluding the study that caused the heterogeneity, with a pooled odds ratio (OR) with a 95% CI equating to 1.97 (1.64, 2.30) [145]. A second meta-analysis, which included 8 studies, found that HCV-infected subjects kept an increased risk of cerebro-CV events (OR, 1.30; 95% CI, 1.10-1.55; P < 0.01) than uninfected subjects, with a stronger impact in those with higher CV risk (e.g., high incidence of T2D or hypertension) [15].…”
Section: Potential Mechanisms Linking Hcv To Atherosclerosismentioning
confidence: 99%